ANALISIS TERHADAP IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN UNTUK ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA EMKM CV. M’ARS STUDIO - Mamengko, Christian Jhon; Saerang, David Paul Elia; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
One indicator that can be done to support the development of an increase in the national economy is through the Micro, Small and Medium Enterprises (EMKM). This study aims to find out about the implementation of financial reporting practices at CV. M’ars Studio, know the statement of financial position at the end of the period (balance sheet), find out the income statement during the period, knowing notes to financial statements during the period, based on EMKM SAK ETAP. The object of the research is the implementation of the EMKM Financial Accounting Standards CV. M’ars Studio. This type of research is qualitative and uses descriptive qualitative methods used in this study are primary data which is data obtained through interviews conducted by researchers on owners and administrators and through direct observation on CV. M’ars Studio besides that, secondary data obtained through evidence of library and documentary studies owned by CV. M’ars Studio. Secondary data obtained through evidence of library and documentary studies owned by CV. M’ars Studio. The results of this study indicate that there are several EMKM IFRS elements that have not been implemented by CV. M’ars Studio. Statement of financial position at the end of the period (balance sheet), which is still simple so the implementation is quite good, the income statement is almost in line with the standard so that the implementation made is good, and notes to financial statements at CV. M’ars Studio have not been implemented. There are major obstacles faced in implementing SAK EMKM, namely the lack of information to the entity regarding IFRDs that apply specifically to MSMEs.